Interfacial negative capacitance in planar perovskite solar cells: An interpretation based on band theory. (November 2018) - Feng, Yulin; Bian, Jiming; Wang, Minhuan; Wang, Shi; Zhang, Chunyang; Dong, Qingshun; Zhang, Bingye; Shi, Yantao
Graphical abstract: Highlights: PSCs with different ETL strategies were characterized by EIS measurement under various conditions. The negative capacitance solely occurred in the moderate frequency region when special conditions are met. A model based on semiconductor band theory was proposed to interpret the corresponding mechanism. This achievement provide important insight into the physical mechanism behind the negative capacitance of PSCs. Abstract: The negative capacitance is a peculiar phenomenon frequently observed in electrochemical impedance spectroscopy (EIS) measurement for perovskite solar cells (PSCs). However, the origin and mechanism of the negative capacitance in PSCs remains ambiguous. Here, planar PSCs with different electron transport layer (ETL) strategies (SnO2, TiO2, or without ETL) were characterized by EIS in a wide range of frequencies under various conditions. The negative capacitance solely occurred in the moderate frequency region as the perovskite layer directly contacted with the conductive SnO2 : F (FTO) substrate under illumination and open-circuit conditions. Based on semiconductor band theory, the origin of negative capacitance to the formation of an inversion layer in the perovskite/FTO interface induced by the interfacial energy band over-bent under illumination and open-circuit conditions. Our study provides important insight into the physical mechanism behind the negative capacitance of PSCs.